Method and types of application of computer graphics - Tusupbekova K.I., Тусупбекова К.И. (Рroblems of engineering and professional education, 2022)
The article analyzes the patterns used in various fields of computer graphics science, new scientific discoveries, the results that it contributes to the development of this science and increasing its degree. As a Computer, a technique of mass application, humanity very quickly spread to all spheres of civilization and became an instrument of everyday life for every family and people. Computer graphics has become an integral part of our life and now, in the era of modern technology, occupies a special place in the creation of three-dimensional graphics, ranging from simple geometric shapes to complex design techniques. Graphic editors attract not only professionals, but also ordinary users. Because graphic editors are not very demanding of mathematical and computer knowledge, programming languages.